2018
DOI: 10.1080/00365521.2018.1430252
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis in patients with ulcerative colitis or Crohn’s disease: a retrospective observational study and review of the literature

Abstract: Altogether 173 patients with occurrence of both IBD and MC were found. The most common finding in our patients was onset of CC in a patient with UC. Although these are likely random associations of two different disorders, MC should be considered in the patient with UC or CD if there is onset of chronic watery diarrhoea without endoscopic relapse of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
(113 reference statements)
1
18
0
Order By: Relevance
“…Several exposures that have been associated with inflammatory bowel disease (IBD), such as non-steroid anti-inflammatory drugs and smoking, have also been associated with CC (1). Interestingly, CC has been described to convert into IBD or vice versa (610). These observations suggest that CC and IBD might have pathophysiologic mechanisms in common.…”
Section: Introductionmentioning
confidence: 99%
“…Several exposures that have been associated with inflammatory bowel disease (IBD), such as non-steroid anti-inflammatory drugs and smoking, have also been associated with CC (1). Interestingly, CC has been described to convert into IBD or vice versa (610). These observations suggest that CC and IBD might have pathophysiologic mechanisms in common.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the scientific literature indicates 58 confirmed cases in the past 30 years of MC diagnosed in patients before or after a diagnosis of IBD 4,5,13. Of these cases, only 11 were of patients diagnosed with LC and UC 4,5,13.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the scientific literature indicates 58 confirmed cases in the past 30 years of MC diagnosed in patients before or after a diagnosis of IBD 4,5,13. Of these cases, only 11 were of patients diagnosed with LC and UC 4,5,13. One case series identified 4 patients with UC in remission who subsequently developed LC, while another case series reported 2 patients initially diagnosed with LC who later developed UC 4,5,13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations